(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Peste des petits ruminants (PPR) is a transboundary, highly contagious, notifiable, viral disease of small ruminants. In recognition of its global threat and socioeconomic impact, the World Organisation for Animal Health (WOAH) and the Food and Agriculture Organization (FAO) have targeted PPR for eradication by 2030, accelerating the need for robust diagnostic, surveillance, and vaccination strategies. This review synthesizes global efforts toward PPR eradication, with a particular focus on diagnostic efficacy, vaccination coverage, and the persistent challenges that hinder progress. It also addresses concerns raised in the 2024 WOAH/FAO technical review regarding potential unintended consequences of eradication—namely, the ecological niche left by rinderpest and PPR that may allow the emergence or spread of other morbilliviruses. A literature search was conducted using peer-reviewed articles (2015–2025) and recent FAO/WOAH reports. Key gaps were identified in vaccine deployment, differentiating infected from vaccinated animals capability, and field diagnostics in addition to the potential unintended consequences of eradication. Finally, we advocate for the integration of predictive modeling to assess the risk of disease reintroduction and host spillover and for embedding these insights into future eradication policies. J. Adv. Vet. Anim. Res., 12(4): 1259–1274, December 2025 http://doi.org/10.5455/javar.2025.l987